Застосування фактологічної реляційної моделі для інтеграції неоднорідних структур даних - Берко, Андрій Юліанович (Eastern-European Journal of Enterprise Technologies, 2009)
Anypossibilitiesofpresentation of heterogeneous and semistructured data inrelation for mareconsidered. Factological relation structure of data has been proposed for solution of this problem.